Successful treatment of massive pulmonary embolism with reteplase - Ali Çoner; Davran Çiçek; Serhat Balcıoğlu; Sinan Akıncı; Haldun Müderrisoğlu (KARE Publishing, 2018)
Unexpected and unexplained out-of-hospital cardiac arrests have a poor prognosis. Difficulties encountered during the differential diagnosis phase may delay the administration of specific treatment for treatable and reversible causes of cardiac arrest. Massive pulmonary embolism is a reversible cause of cardiac arrest, but without proper management it has a high mortality rate. Presently described is the case of a 53-year-old female patient with a massive pulmonary embolism.